Incidence of Tuberculosis and Amyloidosis among Sudanese Patients Presented with Enlarged Nodes - Ahmed Abdalla Agab Eldour; Entisar Najeeb Mohmed Salih; Hussain Gadelkarim Ahmed (Journal of Tropical Medicine)
Objectives. To determine the incidence of tuberculous lymphadenitis and amyloidosis in enlarged lymph nodes (LN). Methodology. A retrospective study was carried out in the department of pathology at the Faculty of Medicine, University of Kordofan, during one-year period. The study included a group of 103 patients with lymphadenopathy. Results. Of the 103 cases with enlarged neck nodes, 35 (34%) had tuberculous lymphadenitis. Sixteen (46%) cases were males and 19 (54%) cases were females. Out of the 103 patients, amyloidosis was diagnosed in 9/103 (8.7%). Out of the 9 positive cases, 2/9 (22.2%) were males and 7/9 (77.8%) were females. Conclusion. There is high incidence of tuberculous lymphadenitis in patients with enlarged LN in developing countries like North Sudan. Amyloidosis should not be ignored when investigating enlarged LN.